The effect of different finishing and polishing systems on surface roughness of new low polymerized composite materials (An in vitro study) - Mustafa R Abdurazaq; Ali H Al-Khafaji (College of Dentistry/ University of Baghdad, 2014)
Background: Prophylaxis methods are used to mechanically remove plaque and stain from tooth surfaces; such methods give rise to loss of superficial structure and roughen the surface of composites as a result of their abrasive action. This study was done to assess the effect of three polishing systems on surface texture of new anterior composites after storage in artificial saliva. Materials and methods: A total of 40 Giomer and TetricN-Ceram composite discs of 12 mm internal diameter and 3mm height were prepared using a specially designed cylindrical mold and were stored in artificial saliva for one month and then samples were divided into four groups according to surface treatment: Group A (control group):10 specimens received no surface polish and were subdivided into A1 (Giomer) and A2 (TetricN-Ceram). Group B: 10 specimens received polishing with Air polishing devise (APD) and were subdivided into B1 (Giomer) and B2 (TetricN-Ceram). Group C: 10 specimens received polishing with pumice and brush and were subdivided into C1 (Giomer) and C2 (TetricN-Ceram). Group D: 10 specimens were polished with pumice and rubber cup and were subdivided into D1 (Giomer) and D2 (TetricN-Ceram). Testing was done by means of profilometer and statistically analyzed using analysis of variance test (ANOVA), LSD and student t-test. Also samples were photographed by special orthoplane camera using light polarizing microscope. Results: The results showed a highly statistical significant difference in surface roughness among Giomer subgroups P